Irsā al-Usus al-‘Ilmīyah li al-Dirāsat al-Islāmīyah: al-Taṭawwur al-Akādīmī li al-Jāmi’at al-Islāmīyah al-Ḥukūmīyah wa al-Ma’āhid al-Islāmīyah al-Ḥukūmīyah al-‘Ulyā bi Indūnīsīyā - Fuad Jabali (Studia Islamika, 2002)
in the past, the main purpose of IAIN was "simply" as a missionary institution, responsible for the dissemination of the Islamic religion throughout the community. However, as it developed, besides remaining as an institute for propagating missionary works, IAIN has also played an increasingly bigger role as an academic institution in the arena of Islamic higher education. Due to this, the oreinetation, efforts and responsibility of IAIN have shifted noticeable into the realm of academia and knowledge building.DOI: 10.15408/sdi.v9i2.668